Questioning punishment - Carvalho, Henrique (Routledge, 2024)
"This book questions punishment as concept, social phenomenon and contemporary practice. It unpacks punishment's nature and the assumptions that underpin it, examines its targets, objectives and implications, locates punishment and punitivity within their social contexts, and aims to unsettle the idea that there is something common-sensical, necessary and unavoidable about punitive justice. Questioning Punishment develops its argument through an innovative structure and is organised around five central questions. It starts by unpacking what punishment is; then considers who punishment's targets and subjects are, how punishment is perpetuated and experienced, when and where punishment unfolds and why we punish. The book ends by considering the implications of this enquiry to understandings of punishment and broader pursuits and conceptualisations of justice. This book is essential reading for all those engaged with the sociology of punishment and prisons, criminal justice, and theoretical criminology"--